MUTATION ON Bacillus subtilis BAC4 USING ACRIDINE ORANGE AS AN EFFORT FOR INCREASING ANTIBIOTIC PRODUCTION - Supartono Supartono; Nanik Wijayati; Lina Herlina; Enny Ratnaningsih (Universitas Gadjah Mada, 2008)
The efforts to get a new antibiotic require to be done continuously, because infection diseases still become the main health problems in Indonesia. A new local strain of Bacillus subtilis BAC4 has been known producing an antibiotic that inhibites Serratia marcescens ATCC 27117 growth. Nevertheless, the optimum conditions have not been studied seriously. The objective of this research was to conduct mutation on B. subtilis BAC4 in order to obtain a mutant cell that overproduct in producing antibiotic. The mutation process was performed by using acridine orange of 1 g.L-1 randomly at various volumes. The production of antibiotic was conducted using batch fermentation and antibiotic assay was performed with agar absorption method using S. marcescens ATCC 27117 as bacteria assay. Research result provided a B. subtilis M10 mutant with overproduction of antibiotic. Characterization of B. subtilis M10 mutant showed that the mutant cell has size of (0.5-1.0) µm x (1.85-2.5) µm; spore has the form of ellipse with thick wavy wall, positive reaction for catalase, and forming acid from glucose and xylose.